Getting a grasp of depression: the road to mental health remedy / Noor Shahariah Saleh and Nurul Syafawani Halim - Saleh, Noor Shahariah; Halim, Nurul Syafawani (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
In early May this year, a houseman at Penang Hospital was discovered deceased after allegedly falling from an office building. He had barely been assigned to the hospital for three weeks when the incident occurred. The police department disregarded the case as a "common" condition, and the cause of death was declared sudden. This situation has sparked outrage among colleagues, with numerous anonymous doctors claiming that bullying was to blame. While people were still talking about this issue, they were surprised by another related news a few days later. Shah Alam's Assistant Commissioner reported that the police department received an emergency call about a 19-year-old girl who claimed to "put her mind at ease" while wandering and later sitting alone on the wall of the fifth floor of a shopping complex. A young man who knew her rushed to the location to check on her after noticing her suspicious picture update on her WhatsApp status. He sensed that this young woman was about to take her own life. Fortunately, the prompt action by the authorities managed to save her from the unwanted event.